2017
DOI: 10.1016/j.jaad.2017.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Circulating vitamin D–binding protein and free 25-hydroxyvitamin D concentrations in patients with melanoma: A case-control study

Abstract: Armstrong et al did not fully report the association between psoriasis and the amount of cigarettes smoked. 2 The association between duration of smoking and psoriasis has been controversial. 2 In this study, we clearly showed that there is a positive correlation between the amount and/or duration of smoking and the occurrence of psoriasis. However, our study has a limitation in that any change in smoking status after registration has not been reflected. In addition, association does not demonstrate cause an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
(2 reference statements)
0
10
0
1
Order By: Relevance
“…Table 2 shows the main characteristics of the other six studies [20][21][22][23][24][25] with 12 297 cases overall reporting the association between serum vitamin D levels and melanoma risk. The total relative ratio for the comparison of serum vitamin D levels between the highest and lowest quantiles was 1.12 (95% CI 0.53 to 2.35) with I 2 =91% (figure 4).…”
Section: Meta-analysismentioning
confidence: 99%
“…Table 2 shows the main characteristics of the other six studies [20][21][22][23][24][25] with 12 297 cases overall reporting the association between serum vitamin D levels and melanoma risk. The total relative ratio for the comparison of serum vitamin D levels between the highest and lowest quantiles was 1.12 (95% CI 0.53 to 2.35) with I 2 =91% (figure 4).…”
Section: Meta-analysismentioning
confidence: 99%
“…While SNPs in VDBP were reported not to influence melanoma survival in a case-control study 50 , meta-analysis of VDBP polymorphisms suggested that VDBP rs12512631 TT genotype was linked to a poorer survival compared with those with TC and CC genotypes 47 . The involvement of VDBP in cancer has a complex mechanism: on one hand, VDBP enhances epithelial ovarian cancer progression 51 , on the other hand, higher circulating VDBP levels were observed in healthier melanoma patients 52 . Also, a meta-analysis including 28 studies of 12 different cancers, and analyzing VDBP protein levels vs. cancer risk found trends toward significance (lower risk related to high expression), suggesting a role of VDBP in cancer etiology 53 .…”
Section: Resultsmentioning
confidence: 99%
“…The level of serum vitamin D circulating in the blood is best examined as 25 (OH) vitamin D. In many recent studies, serum 25-Hydroxyvitamin D levels are low in many different cancer types and inflammatory patients compared to the control group (5,16). In this context, the vitamin D level in gastrointestinal tract cancers (such as the stomach, large intestine) was found lower than the control group and were associated with poor prognosis (17). In the same way, it is claimed that there is a low vitamin D level in chronic inflammation and there is a connection between inflammation severities (18).…”
Section: Discussionmentioning
confidence: 99%